Az iszaplerakódás sorsa a római földmérés és jog tükrében - Takács, Levente (Debreceni Jogi Műhely, 2010)
Besides legal sources, the term alluvio appears in Roman surveyors’ works and to a lesser extent in literary pieces. Chronologically, the word was used later in literary works than by surveyors and legal sources. Legal usage had definitely influenced literary usage. However, the meaning of the term had undergone some change during the word borrowing process. The Digesta and Institutiones first define the term, then deal with this doctrine in connection to usufruct, pledge, will and sale. Legal sources are well complemented and tinged by the Roman surveyors’writings, who examined the problem of alluvio from technical and legal aspects as well. For example their writings provide essential information about which parts of the Roman Empire were affected regularly by the action of rivers. The collation of sources makes it possible to examine the problem of alluvio from historical aspect as well, which is closely connected to the assessment of river bank land. It seems probable that as a result of a long process the distinction made between ager occupatorius and ager limitatus became less important from the point of view of alluvial accession.